Pemanfaatan Pembangkit Listrik Tenaga Surya untuk Penerangan Jalan Umum (PJU) di Desa Drawati - Ariyapijati, Raden Hendra; Susetyo, Budi; Wibawa, Satria (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2025)
This community service program aims to improve public street lighting (PJU) access for residents of Drawati Village, Paseh District, Bandung Regency, through the utilization of renewable energy in the form of solar power. The main issue faced by the community is the lack of adequate lighting at night, which negatively affects social activities, neighborhood safety, and residents' comfort. The implementation method includes needs assessment, technical planning, procurement of solar-powered street lighting equipment, installation at strategic points, and community education on usage and basic maintenance. A total of five solar-powered streetlight units were successfully installed in locations agreed upon with local leaders and village officials. The results of the activity indicate a notable improvement in the community’s quality of life, particularly in terms of nighttime safety and increased outdoor activities after dark. Moreover, this initiative has raised community awareness of the importance of using clean and environmentally friendly energy. In conclusion, the application of simple technology such as solar streetlights can create a significant social impact and should be further developed through maintenance training and the empowerment of local communities to sustain the installed infrastructure.